Micro- and nano-plastics activation of oxidative and inflammatory adverse outcome pathways - Moyan Hu; Dušan Palić (Redox Biology, 2020)
Microplastics (MPs) and nanoplastics (NPs) have attracted considerable attention in the recent years as potential threats to the ecosystem and public health. This review summarizes current knowledge of pathological events triggered by micro- and nano-plastics (MP/NPs) with focus on oxidative damages at different levels of biological complexity (molecular, cellular, tissue, organ, individual and population). Based on published information, we matched the apical toxicity endpoints induced by MP/NPs with key event (KE) or adverse outcomes (AO) and categorized them according to the Adverse Outcome Pathway (AOP) online knowledgebase. We used existing AOPs and applied them to highlight formal mechanistic links between identified KEs and AOs in two possible scenarios: first from ecological, and second from public health perspective. Ecological perspective AOP based literature analysis revealed that MP/NPs share formation of reactive oxygen species as their molecular initiating event, leading to adverse outcomes such as growth inhibition and behavior alteration through oxidative stress cascades and inflammatory responses. Application of AOP on literature data related to public health perspective of MP/NPs showed that oxidative stress and its responding pathways, including inflammatory responses, could play the role of key events. However insufficient information prevented precise definitions of AOPs at this level. To overcome this knowledge gap, further mammalian model and epidemiological studies are necessary to support development and construction of detailed AOPs with public health focus.